INDUKSI PEMIJAHAN SEMI ALAMI DENGAN KOMBINASI HORMON SPAWNPRIME DAN OVASPEC PADA IKAN PERES (Osteochilus kappeni) - lijana, Lijana; Faisal, Teuku Muhammad; Komariyah, Siti (Universitas Teuku Umar, 2021)
This study aims to analyze the combination of Spawnprime and Ovaspec hormones on the gonad maturity process and the broodstock of Peres fish (Osteochilus kappeni). The method used was a completely randomized design (CRD) with 4 treatment levels and 3 replications. The results showed that the combination of Spawnpriment Hormones and Ovaspec in Peres broodfish had a significant effect on IKG, Fecundity, Degree of Fertilization, and Degree of Hatching. However, the increase in absolute weight and egg diameter of Peres fish had no significant effect. The results showed that the combination of Spawnprime and Ovaspec hormones in Peres broodfish had a significant effect on IKG P4 9.16%, P3 8.41%, P2 7.36%, P1 0%. Fecundity P3 11057.54 items, P4 9351.43 items, P2 9210.0 items, P1 0 items. The degree of conception P4 96.00%, P3 95.33, P2 80.33, P1 0%. And the degree of hatching P4 97.93%, P3 92.74, P2 91.70, P1 0%. However, it did not significantly affect the increase in absolute weight P1 4.00 g, P4 3.50 g, P3 and P2 have the same value, namely 3.33 m. Egg diameter P1 0.36 mm, P2 0.33 mm, P2 0.32 mm and 0.29 mm.